Potential prophylactic role of silicon against brown rust (Puccinia melanocephala) in sugarcane - Camargo, Mônica Sartori; Coutinho, Isabel D. [UNESP]; Lourenço, Silvia A.; Soares, Marli K. M.; Colnago, Luiz A.; Appezzato-da-Glória, Beatriz; Cavalheiro, Alberto J. [UNESP]; Amorim, Lilian (Springer Nature, 2020)
Some benefits of silicon (Si) fertilization have been reported in sugarcane plants, but information about the effects of Si on brown rust (Puccinia melanocephala) remain scarce, even though this plant disease is widespread in several areas around the world. The objective of this study was to evaluate whether Si potentiates the production of antimicrobial metabolites in sugarcane plants in response to infection by P. melanocephala. Experiments with a sugarcane cultivar (SP70–1143) susceptible to brown rust were conducted in pots (3 L) under greenhouse conditions using a randomized complete block design with four treatments: with and without Si (equivalent to 0 and 800 kg ha−1 of Si, denominated -Si and + Si, respectively), sprayed with water or inoculated with a suspension of P. melanocephala urediniospores. Liquid potassium silicate was applied in soil as a source of Si. Si fertilization increased soil Si and Si concentration in plants, which correspondingly decreased brown rust severity and sporulation of P. melanocephala in leaves. Silicon fertilization increased the concentration of sucrose and cis-aconitic acid and reduced the concentration of chlorogenic acid (trans-3-caffeoylquinic acid) in sugarcane leaves inoculated with the pathogen. In vitro germination of P. melanocephala was reduced in contact with all metabolites isolated by UHPLC-DAD (chlorogenic acid and C-glycosylated flavones) from the sugarcane leaves. This work helps to elucidate the potential prophylactic role of Si in the interaction between P. melanocephala and sugarcane.
Keywords: Brown rust; Disease; Metabolites; Nutrition; Saccharum hybrids